Effect of Thermal Stress on Serum Biochemical and Haematological Parameters in Broiler Chicken - Jaiswal, Sudhir Kumar; Raza, Meesam; Chaturvedani, A. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted to assess the effects of thermal stress on the serum biochemical and haematological parameters in broiler chicken. Forty CARIBRO- Vishal broiler chicken were divided into two groups with twenty birds each. The control group was kept at room temperature and treatment group was exposed to thermal stress under 40±1 °C for 4 hours at 35 day of age. The exposure of thermal stress significantly increased (P
Keywords: Thermal stress; Biochemical; Haematological parameters; Broiler chicken